2014
DOI: 10.1007/s40620-013-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic calcification and renal resistive index in patients with chronic kidney disease: is there a connection?

Abstract: As Kauppila score correlates with RRI in non-dialysis CKD patients, it could be a fast, convenient and relatively inexpensive tool for estimating RRI, and consequently the intrarenal vascular status, but further research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…According to the authors, another pathophysiological explanation for the correlation between AAC and RRI is that systemic vascular calcification, especially renal artery calcification, impairs renal blood flow, thus increasing RRI. The present study demonstrated an association between AAC and RRI, thus offering more robust evidence for the association between vascular calcification and RRI [24]. The present study also established a correlation between age and increase in RRI.…”
Section: Discussionsupporting
confidence: 81%
“…According to the authors, another pathophysiological explanation for the correlation between AAC and RRI is that systemic vascular calcification, especially renal artery calcification, impairs renal blood flow, thus increasing RRI. The present study demonstrated an association between AAC and RRI, thus offering more robust evidence for the association between vascular calcification and RRI [24]. The present study also established a correlation between age and increase in RRI.…”
Section: Discussionsupporting
confidence: 81%
“…In a recent study of 77 CKD subjects, abdominal aortic calcifications were directly related to RRI (r Z 0.35 p < 0.001) and cIMT (r Z 0.27 p Z 0.01) [26]. Furthermore, several studies found correlations between arterial wall calcifications and systemic atherosclerotic damage, especially in CKD patients [27].…”
Section: Discussionmentioning
confidence: 94%
“…Vascular calcifications of the large arteries, like abdominal aorta (assessed by the lumbar aortic calcification score-ACS) is not only a predictor of the cardiovascular morbidity and mortality, but it could also provide an indirect estimation of the intrarenal vascular status, as we found in a cross-sectional study that enrolled 77 stages 2-5 non-dialysis CKD patients, older than 50 years, and with known atherosclerotic disease. This study described increased aortic calcification as eGFR declines and found that higher lumbar aortic calcification score was independently associated with lower ankle-brachial index and higher intima-media thickness, suggesting a relationship of abdominal calcifications with the extension of atherosclerosis in other territories [85]. In addition, the novel finding of the study was the ability of an aortic calcification score >5 to predict with 65% sensitivity and 68% specificity a pathologic (<0.7) renal resistive index (marker of intrarenal atherosclerotic lesions on Doppler ultrasound) [85].…”
Section: Atherosclerotic Cardiovascular Diseasementioning
confidence: 82%
“…This study described increased aortic calcification as eGFR declines and found that higher lumbar aortic calcification score was independently associated with lower ankle-brachial index and higher intima-media thickness, suggesting a relationship of abdominal calcifications with the extension of atherosclerosis in other territories [85]. In addition, the novel finding of the study was the ability of an aortic calcification score >5 to predict with 65% sensitivity and 68% specificity a pathologic (<0.7) renal resistive index (marker of intrarenal atherosclerotic lesions on Doppler ultrasound) [85].…”
Section: Atherosclerotic Cardiovascular Diseasementioning
confidence: 82%